Nestin expression in repopulating mesangial cells promotes their proliferation - Daniel, Christoph; Albrecht, Heinz; Lüdke, Andrea; Hugo, Christian (Laboratory Investigation, 2008)
We investigated whether the intermediate filament protein and neural stem cell marker nestin characterizes the glomerular progenitor/reserve cell population immigrating the glomerulus after mesangial cell (MC) injury in the rat (anti-Thy1 nephritis). Nestin expression was investigated by immunohistochemistry and real-time PCR during anti-Thy1 nephritis. Migration and proliferation assays were used to characterize the function of nestin in isolated MCs after nestin knockdown by siRNA. After MC injury during anti-Thy1 nephritis, glomerular nestin was transiently increased during the repopulation phase. At the peak of mesangial proliferation and expansion (day 5) most OX-7-positive MCs expressed nestin largely colocalizing with the activation marker α-smooth muscle actin and the proliferation marker PCNA. In contrast to a healthy, non-injured mesangium in vivo, MCs in culture are considered to be in an 'activated, injured state' and express nestin in a generalized distribution with condensed localization around the nucleus as well as intensive staining of cell protrusions such as filopodia. During cell cycle, the percentage of MCs with high nestin levels was increased during S- aupnd G2-phase. Blocking of nestin using specific siRNA resulted in inhibition of cell proliferation but not cell migration. In conclusion, nestin is constitutively expressed in podocytes, but is a marker for repopulating MCs after experimental MC injury in vivo. Nestin promotes MC proliferation in vitro, suggesting a supporting role for nestin during repair reaction. © 2008 USCAP, Inc All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Nestin; Podocytes; Proliferation; Repopulation; Stem cells